The Auditory Steady-State Response: Comparisons with the Auditory Brainstem Response - Cone-Wesson, Barbara; Dowell, Richard C.; Tomlin, Dani; Rance, Gary; Ming, Wu Jia (Journal of the American Academy of Audiology, 2002)
Two studies are reported in which the threshold estimates from auditory steady-state response (ASSR) tests are compared to those of click- or toneburst-evoked auditory brainstem responses (ABRs). The first, a retrospective review of 51 cases, demonstrated that both the click-evoked ABR and the ASSR threshold estimates in infants and children could be used to predict the pure-tone threshold. The second, a prospective study of normal-hearing adults, provided evidence that the toneburst-evoked ABR and the modulated tone–evoked ASSR thresholds were similar when both were detected with an automatic detection algorithm and that threshold estimates varied with frequency, stimulus rate, and detection method. The lowest thresholds were obtained with visual detection of the ABA. The studies illustrate that ASSRs can be used to estimate pure-tone threshold in infants and children at risk for hearing loss and also in normal-hearing adults.
Keywords: Auditory; evoked potentials; auditory threshold